Narrative identity construction and talents education in adolescence: an investigation into the transformative power of storytelling - Olivieri, Diana (Formazione & insegnamento, 2020)
The idea that people create an identity – conceptualized in terms of beliefs, ideological commitments, social roles and personal talents – through the construction of stories has emerged, in recent decades, as a leading concept in social sciences. Given this ideological convergence on the importance of narrative for the construction of identity, it was therefore decided to analyze adolescent narrative strategies to capture the construction of identity and the interpretation of the self in adolescence. In particular, a narrative perspective as a methodological tool proves suitable for the study of both risk and vulnerability issues, as well as potentiality and talent in adolescence, since narrative – as a psychosocial construction – can shed light on the intersections of the adolescent with his cultural, professional and family contexts (Bruner 1990). The present investigation therefore has two objectives: 1) to investigate how it is possible to promote the development of narrative identity, both at school and after school level, as a strategy for conscious and critical construction of one’s Self, in the perspective of a facilitation of talent training in adolescence; 2) to document how the narrative process contributes to the formation of vocational identity, recognized as an important milestone in the transition from school to the world of work.